Pengaruh Lokasi dan Kepuasan Terhadap Loyalitas Pelanggan Pada Rumah Makan Nanda Soto Sei Blutu Medan - Mitha Lestari; Amrin Mulia U Nasution; Adelina Lubis (Universitas Medan Area, 2020)
This study aims to determine the Influence of Location and Satisfaction Against Customer Loyalty At Restaurant Nanda Soto Sei Blutu Medan. This type of research is associative. The population in this study is were 900 people and by using the technique Random Sampling, then the number of samples in this study as many as 90 respondents. Based on the result of research that location variable has a positive effect on loyalty variable with a value 2.646 and ha a significant value of 0.00 0.05 significant meaning. And satisfaction has a positive effect on loyalty variable with a value 2.542 and ha a significant value of 0.01 0.05.